PENGARUH CLOSED KINETIC CHAIN EXERCISE DAN OPEN KINETIC CHAIN EXERCISE TERHADAP AKTIVITAS FUNGSIONAL PADA PASIEN OSTEOARTHRITIS KNEE DI RUMAH SAKIT GRANDMED LUBUK PAKAM TAHUN 2022 - BERAMPU, SURYA SYAHPUTRA (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2022)
Osteoarthritis is the most common degenerative condition among the elderly. Functional disorders are caused by knee osteoarthritis. A person with osteoarthritis knee typically experiences pain, stiffness, and a decrease in functional activity as a result of limited function. The purpose of this study is to compare the effects of open kinetic chain exercise and closed kinetic chain exercise on increasing functional activity in patients with osteoarthritis of the knee. This is a quasi-experimental type of study. To compare two intervention groups, a two-group pre-test post-test research design was used. In addition, WOMAC is being used to assess functional ability. Exercises should be done twice a week for four weeks. Effect analysis using the paired T-test in treatment groups 1 and 2. The paired T-test on closed kinetic chain exercise and open kinetic chain exercise yielded the same result, P = 0.000 (p0.05), indicating that functional ability influences before and after treatment. Meanwhile, an independent t-test resulted in a value of p = 0.153 (p>0.05), indicating that there are differences in the influence of open kinetic chain and closed kinetic chain on increasing functional ability in patients with osteoarthritis knee. Open kinetic chain exercise and closed kinetic chain exercise have different effects on improving functional ability in people with osteoarthritis knee.